2013
DOI: 10.1007/s10620-013-2746-2
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Age, and Gender Affect Prep Quality, Sedation Use, and Procedure Time During Screening Colonoscopy

Abstract: Normal-weight females, particularly those under age 60, have the lowest APR but have longer procedure times and require higher amounts of sedation. Screening options other than colonoscopy might be well-suited to this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
12
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
4
12
1
Order By: Relevance
“…The association of female sex with the primary outcome for colonoscopy but not for OGD may be explainable by differences in anatomy related to colonoscopy. It has been previously described that female sex is associated with an increased risk of abdominal discomfort during colonoscopy as compared to men, and that females receive higher sedative medication doses for conscious sedation during screening colonoscopy . This is consistent with our findings, and supports the idea that this could be due to increased pain during colonoscopy in females, perhaps due to increased tortuosity of the colon due to female reproductive anatomy, or greater colon length that has been described in women …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The association of female sex with the primary outcome for colonoscopy but not for OGD may be explainable by differences in anatomy related to colonoscopy. It has been previously described that female sex is associated with an increased risk of abdominal discomfort during colonoscopy as compared to men, and that females receive higher sedative medication doses for conscious sedation during screening colonoscopy . This is consistent with our findings, and supports the idea that this could be due to increased pain during colonoscopy in females, perhaps due to increased tortuosity of the colon due to female reproductive anatomy, or greater colon length that has been described in women …”
Section: Discussionsupporting
confidence: 92%
“…A study published in 2005 found that pre‐procedure anxiety and use of psychotropic drugs or alcohol were associated with an ‘adverse endoscopic experience’ . An additional study ( n = 773) investigated BMI, age and gender in relation to CRC screening colonoscopy preparation quality, sedation use, and procedure time and found that decreasing age and female sex were associated with higher doses of sedative medications . A previous study by our group showed that patients with coeliac disease have higher sedative dose requirements during OGD and colonoscopy than those without coeliac disease .…”
Section: Discussionmentioning
confidence: 97%
“…Despite their conclusion that colonoscopy was less efficacious and more risky [9] for younger women with normal BMI than for their male counterparts, colonoscopy may remain the optimal screening modality compared with other methods. For example, a comparison of hypothetical flexible sigmoidoscopy with total colonoscopy reported that the former could detect lesions in only 35 % of women with proximal neoplasia [10], suggesting that colonoscopy may be the optimal CRC screening tool for women.…”
mentioning
confidence: 98%
“…In the study published by Czwornog et al [9] in this issue of Digestive Diseases and Sciences, the authors concluded that normal-weight females (particularly those under age 60) have the lowest adenoma prevalence rate (APR) but have longer procedure times and require higher amounts of sedation. Those results, consistent with previous reports and our clinical practice, indicated that the APR in such subjects was 17.9 %, meaning that colonoscopic screening is beneficial for only the 17.9 % of normal weight females younger than 60 years old, but can be harmful for the remaining 82.1 % due to longer procedural times and the greater use of sedatives.…”
mentioning
confidence: 99%
See 1 more Smart Citation